Adaptation of foreign first-year students of a military academy to the educational process as a pedagogical problem - Olga A. Voskrekasenko; Olga A. Buchneva (Высшее образование в России)
The article deals with some peculiarities of adaptation of foreign first-year students of a military academy to the educational process. Special attention is paid to the characteristics of some factors, which cause difficulties during foreign first-year academy students adaptation. Some directions of pedagogical support of their adaptation are considered.